Pengaruh Pembelajaran Problem Solving Modifikasi Terhadap Kemampuan Komunikasi Matematis - Dina Nurhasanah; Rizki Wahyu Yunian Putra (De Fermat : Jurnal Pendidikan Matematika, 2020)
Mathematical communication skills are essential for learners in math learning. Increased numerical ability of students impact on the results of the study aims to determine whether there is improvement in the mathematical communication skills of learners by using methods learning problem solving modification. Method used is quantitative method. The types of research used are Quasy experiments and design experiments used in the design of non-equivalence control groups and data analysis used with one way Anava. The results of the study are Fhitung = 11,186, Ftabel = 3.09 then H0 rejected, then it can be concluded the research has an influence that is not equal to the mathematical communication skills of learners.